Impact Of Sosial And Entrepeneurial Stigma To The Performance Of Female Entrepreneur Moderated By The Occurrence Of Psychological Capital - Maimunah, Nia; Rahman, Hafiz; Fahmy, Rahmi (Journal Research of Social Science, Economics, and Management, 2023)
Nowsday there are still many people think that women who work other than being housewives will not be as successful as men. the interaction between an individual and their social environment such as family, friends or relatives plays an important role in developing entrepreneurial intentions. This study aims to determine whether social stigma and entrepreneurial stigma have an effect on performance of female entrepreneurs. This research investigated whether psychological capital could act as moderators. The purpose of this quantitative approach is to examine the relationship between Exogenous latent variables, moderation variable and the dependent variable in order to determine whether the variable has a significant effect on other variables. For the method used in this nonprobability sampling and the author uses Area Sampling. The result of this study found that Social stigma and entrepreneur stigma negatively and significantly affects to entrepreneurial performance.